Building sustainable and resilient agri-food systems under multiple shocks - Liu, Jianguo; Winkler, Julie A.; Ross, R. Brent; Viña, Andrés; Frank, Kenneth A.; Konar, Megan; Liang, Chyi-lyi; Marshall, Maria I.; Nichols, Sue; Robinson, Jennifer Meta; Varshney, Lav R.; Whipple, Judith M.; et al. (Frontiers in Sustainable Food Systems, 2025)
Shocks, such as disease outbreaks, extreme weather events, cyberattacks, financial crises, and wars, are occurring with greater frequency. When these shocks occur simultaneously and/or in sequence, referred to here as multiple shocks, they can generate compound impacts on agri-food systems and contribute to food and nutrition insecurity. Building sustainable agri-food systems that are resilient to multiple shocks requires an integrated understanding of the threats posed by multiple shocks to all aspects of supply chain networks. Collective action by researchers, educators, extension experts, and other stakeholders can mitigate and improve adaptation to these impacts. However, there are major knowledge gaps in examining, understanding, and synthesizing agri-food systems under multiple shocks. Previous actions have been fragmented, as efforts have largely focused only on an individual shock, in a specific place, and with separate rather than integrated efforts in research, education, and extension. Here, we present an integrated framework to address multiple shocks toward enhancing agri-food system resilience and sustainability. We illustrate how this integrated framework can be operationalized, focusing on assessing impacts, identifying mitigation strategies, providing decision support, training a future agri-food system workforce, and building communities for resilience to multiple shocks. Finally, we discuss challenges and opportunities in applying the framework for enhancing agri-food system resilience and sustainability worldwide, thus contributing to the realization of several United Nations Sustainable Development Goals, particularly SDG 2 (Zero Hunger).